Effects of Barley (Hordeum vulgare L.) on Antioxidant Activities of Maillard Reaction Products and Consumer Acceptance of Barley Nurungji, Traditional Korean Snack - Yerim Jeong; Il Sook Choi (Foods)
This study evaluated the physicochemical characteristics, antioxidant properties, and consumer acceptance of a traditional Korean snack nurungji blended with barley (Hordeum vulgare L.). The antioxidant activity of β-glucan was identified in barley using a model Maillard reaction products (MRPs) system. Nurungji samples were analyzed based on barley cultivars (waxy and hulled), barley blending ratios (0, 25, 50, 75, and 100), and cooking equipment (electric and electric pressure rice cooker). Nurungji blended with waxy barley and cooked using an electric pressure rice cooker showed a significant increase in antioxidant properties, such as 2,2-diphenyl-1-picrylhydrazyl and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activities, ferric reducing antioxidant power, and reducing power. The antioxidant activity of the model MRP solutions increased according to heating time and the addition of β-glucan. In the consumer acceptance test, nurungji blended with 50% barley showed a significantly higher acceptance rate in terms of overall evaluation, aroma, taste, texture, aftertaste, and purchase intents.